1998
DOI: 10.2337/diabetes.47.6.961
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of sorbitol dehydrogenase deficiency on nerve conduction in experimental diabetic mice.

Abstract: In this report, we made use of sorbitol dehydrogenase (SDH)-deficient mutant mice (C57BL/LiA) to test whether there is a close correlation between the level of polyol accumulation and the degree of reduction in motor nerve conduction velocity (MNCV) associated with diabetes. The C57BL/LiA mouse has SDH deficiency due to a G-to-A mutation at the +1 position of intron 8, thus producing only aberrant SDH transcripts. These C57BL/LiA mice should have higher levels of polyol accumulation in the peripheral nerve bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 0 publications
2
48
0
2
Order By: Relevance
“…This is somewhat surprising since it has been shown that SD inhibition using an SD inhibitor, CP470711, can protect ischemic myocardium (Hwang et al, 2003). However, our previous studies on SD À/À mice in experimental diabetes suggested that SD is not a major culprit in the pathogenesis of diabetic neuropathy (Ng et al, 1998). …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is somewhat surprising since it has been shown that SD inhibition using an SD inhibitor, CP470711, can protect ischemic myocardium (Hwang et al, 2003). However, our previous studies on SD À/À mice in experimental diabetes suggested that SD is not a major culprit in the pathogenesis of diabetic neuropathy (Ng et al, 1998). …”
Section: Discussionmentioning
confidence: 97%
“…C57BL/6N mice were also used in experiments with drug treatment. In addition, SD À/À (C57BL/LiA) mice and their age-matched wild-type controls (SD + / + ) were generated by crossing of the SD heterozygous mice (Ng et al, 1998). All animals used were male mice and were housed under diurnal lighting condition and allowed access to food and water ad libitum.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous preclinical studies have demonstrated that inhibition of aldose reductase (the first enzyme in the polyol pathway) prevents almost all manifestations of neuropathy. Studies in which expression of enzymes involved in the polyol pathway has been manipulated have placed a particular focus on the metabolic consequences of excessive metabolism of glucose to sorbitol owing to high activity of aldose reductase [35][36][37][38] . On the basis of the involvement of the polyol pathway, the perception of diabetic neuropathy as a micro vascular complication of diabetes has been underpinned by immunocytochemical studies that showed localization of aldose reductase to the endothelial cells of epineurial and dorsal root ganglion blood vessels and to perivascular sympathetic axons [39][40][41] .…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…According to the concept of ªdiabetic pseudohypoxiaº [28], the increased flux through SDH accounts for NAD-redox imbalances (increase in NADH:NAD + ratio) related to diabetes and constitutes a universal mechanism for development of diabetic complications including neuropathy, retinopathy and nephropathy. Studies of the role for SDH in diabetic complications using SDH inhibitors (SDIs) [4,30,31] as well as a SDH-deficient mouse model [32] resulted in contradictory findings. Some groups [29±31] have reported that SDIs reduce nerve conduction deficit induced by diabetes.…”
mentioning
confidence: 99%